2015
DOI: 10.1073/pnas.1519735112
|View full text |Cite
|
Sign up to set email alerts
|

Shifting the feeding of mice to the rest phase creates metabolic alterations, which, on their own, shift the peripheral circadian clocks by 12 hours

Abstract: The molecular mechanisms underlying the events through which alterations in diurnal activities impinge on peripheral circadian clocks (PCCs), and reciprocally how the PCCs affect metabolism, thereby generating pathologies, are still poorly understood. Here, we deciphered how switching the diurnal feeding from the active to the rest phase, i.e., restricted feeding (RF), immediately creates a hypoinsulinemia during the active phase, which initiates a metabolic reprogramming by increasing FFA and glucagon levels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
89
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 27 publications
8
89
0
Order By: Relevance
“…S1 C and D and In RF Mice, the Expression of PCC-Controlled Output Genes Is Shifted by 12 h with Respect to the Diurnal Active and Rest Phases Controlled by the Central SCN CC), we explored the molecular basis of its maintenance and found that the active phase RF hypoinsulinemia is a recurring event during long-term RF regime ( Fig. 1A and In RF Mice, the Expression of PCC-Controlled Output Genes Is Shifted by 12 h with Respect to the Diurnal Active and Rest Phases Controlled by the Central SCN CC), which, as expected (5,11), leads to an increase in GSK3β-mediated phosphorylated RevErbα (pRevErbα) level at "Zeitgeber" (ZT) 0 ( Fig. 1 E and F and Fig.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…S1 C and D and In RF Mice, the Expression of PCC-Controlled Output Genes Is Shifted by 12 h with Respect to the Diurnal Active and Rest Phases Controlled by the Central SCN CC), we explored the molecular basis of its maintenance and found that the active phase RF hypoinsulinemia is a recurring event during long-term RF regime ( Fig. 1A and In RF Mice, the Expression of PCC-Controlled Output Genes Is Shifted by 12 h with Respect to the Diurnal Active and Rest Phases Controlled by the Central SCN CC), which, as expected (5,11), leads to an increase in GSK3β-mediated phosphorylated RevErbα (pRevErbα) level at "Zeitgeber" (ZT) 0 ( Fig. 1 E and F and Fig.…”
Section: Resultssupporting
confidence: 63%
“…We recently elucidated (5) how the RF-induced decrease in insulin (INS) blood level during the active phase triggers an aberrant activation of nuclear receptor subfamily 1, group D, member 1 (Nr1d1/RevErbα) through phosphorylation by active glycogen synthase kinase 3β (GSK3β; Fig. 1F) (5). This RevErbα phosphorylation prevents its proteasome degradation (10) and is crucial for the repression of RORα/RevErbα response element (RORE)-DNA binding sequence (DBS)-containing genes (e.g., Bmal1, Cry1), which is a critical event in the initiation of the RF-induced shift of PCCs (5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations